Cardiovascular events during carfilzomib therapy for relapsed myeloma: practical management aspects from two case studies. Issue 10 (26th November 2017) - Jakubowiak, Andrzej J.; DeCara, Jeanne M.; Mezzi, Khalid
ABSTRACT: Objectives and importance : Patients with multiple myeloma (MM) have an increased risk of cardiovascular comorbidities due to disease burden and treatment-related risk factors. Proteasome inhibitors, including bortezomib and carfilzomib, are effective and generally well tolerated anti-MM agents. However, cardiovascular-related toxicities have been reported with this class of agents, the mechanisms of which are not fully understood. We discuss the practical management of cardiovascular events during carfilzomib therapy for relapsed MM. Clinical presentation : We present two adapted cases of treatment-emergent cardiovascular events in patients receiving an approved regimen of carfilzomib for the treatment of relapsed MM. These cases are reflective of clinical practice at the University of Chicago Medicine. Intervention : Using the two adapted cases, we discuss and illustrate practical approaches for management of cardiovascular events during carfilzomib therapy, including baseline cardiac risk assessment, hydration, cardiovascular monitoring, and interventions for patients with suspected cardiovascular signs or symptoms, and patient education. Conclusion : Carfilzomib has a favorable benefit-risk profile in MM; adopting proactive practices can assist in the prevention, early detection, and management of carfilzomib-associated cardiovascular events, which may allow for continuation of therapy with this effective agent.